The impact of protective face coverings on acoustic markers in voice: a systematic review and meta-analysis - Latoszek, Ben Barsties von; Jansen, Viktoria; Watts, Christopher R.; Hetjens, Svetlana (Journal of Clinical Medicine, 2023)
Background: Wearing respiratory protective masks (RPMs) has become common worldwide, especially in healthcare settings, since the onset of the COVID-19 pandemic. Hypotheses have suggested that sound transmission could be limited by RPMs, which possibly affects the characteristics of acoustic energy and speech intelligibility. The objective of this study was to investigate the effect of RPMs on acoustic measurements through a systematic review with meta-analysis. Methods: Five database searches were conducted, ranging from their inception to August 2023, as well as a manual search. Cross-sectional studies were included that provided data on widely used gender-independent clinical acoustic voice quality measures (jitter, shimmer, HNR, CPPS, and AVQI) and habitual sound pressure level (SPL). Results: We found nine eligible research studies with a total of 422 participants who were compared both without masks and with different types of masks. All included studies focused on individuals with vocally healthy voices, while two of the studies also included those with voice disorders. The results from the meta-analysis were related to medical/surgical and FFP2/(K)N95 masks. None of the acoustic measurements showed significant differences between the absence and presence of masks (p > 0.05). When indirectly comparing both mask types, statistical significance was identified for parameters of jitter, HNR, CPPS and SPL (p < 0.001). Conclusions: The present meta-analysis indicates that certain types of RPMs have no significant influence on common voice quality parameters and SPL compared to recordings without masks. Nevertheless, it is plausible that significant differences in acoustic parameters might exist between different mask types. Consequently, it is advisable for the clinical practice to always use the same mask type when using RPMs to ensure high comparability and accuracy of measurement results.
Veröffentlicht: 12. September 2023
Gesehen am 23.11.2023